Analisis Kandungan Merkuri (Hg) pada Air, Sedimen, Ikan Keting (Arius caelatus), dan Ikan Mujair (Oreochromis mossambicus) di Kali Jagir Surabaya [Analysis Of Mercury (Hg) in Water, Sediment, Keting Fish (Arius caelatus), and Mujair Fish (Oreochromis mossambicus) In Jagir River Surabaya] - Boedi Setya Rahardja; Friska Marsyalita; Yudi Cahyoko (Faculty of Fisheries and Marine Universitas Airlangga, 2012)
Abstract Mercury (Hg) is one kind of harmful and toxic heavy metals are very harmful to the lives of both humans and other living things. Surabaya River is one of the branches of the Brantas river, in Wonokromo divided into Mas and Jagir river (Wonorejo) each lead in the Madura Strait. According Sardjono (2012) Surabaya river water was found to contain Hg which implies 100 times higher than the existing standards. The purpose of this study was to determine the levels of mercury (Hg) in water, sediment, keting fish (Arius caelatus), and mujair fish (Oreochromis mossambicus) in Jagir Surabaya river. The research method is descriptive method with sampling obtained at three stations and three replications. These results indicated that the average content of mercury (Hg) in the water of Jagir Surabaya river was at 0.0063 ppm and below threshold. The average content of mercury (Hg) in sediments Jagir Surabaya river was at 0.1433 ppm and below threshold by American standards, was above the threshold by Canadian standards. The average content of mercury (Hg) in keting fish (Arius caelatus) of Jagir Surabaya river was at 0.0096 ppm and below threshold. The average content of mercury (Hg) in mujair fish (Oreochromis mossambicus) in the Jagir Surabaya river was at 0.0112 ppm and below threshold.